Dynamics of Retinal Vessel Loss After Acute Optic Neuritis in Patients With Relapsing Multiple Sclerosis. Issue 3 (17th May 2022) - Aly, Lilian; Noll, Christina; Wicklein, Rebecca; Wolf, Elisabeth; Romahn, Eva Feodora; Wauschkuhn, Josphine; Hosari, Sami; Mardin, Christian; Berthele, Achim; Hemmer, Bernhard; Korn, Thomas; Knier, Benjamin
Abstract : Background and Objectives: Rarefication of the retinal vasculature as measured by optical coherence tomography angiography (OCT-A) is a novel finding in patients with multiple sclerosis (MS). This study aimed to analyze longitudinal dynamics of the retinal vasculature following an acute inflammatory relapse including acute optic neuritis (ON) and to search for associations with alterations of the retinal architecture and visual function. Methods: This prospective longitudinal cohort study included patients with relapsing-remitting MS or clinically isolated syndrome having an acute ON (n = 20) or a non-ON relapse (n = 33). Patients underwent examinations at baseline and after 7, 14, 28, 90, and 180 days with OCT, OCT-A, and assessment of the high- (HCVA) and low-contrast visual acuity (LCVA). Results: Retinal vessel loss of the superficial vascular complex (SVC) evolves early after ON and reaches a plateau between 90 and 180 days (relative vessel loss 15% ± 8% [mean ± SD]). In addition, an 18% ± 18% intraindividual increase of the foveal avascular zone (FAZ) is evident within 180 days after acute ON. Both SVC thinning and FAZ enlargement were associated with worse HCVA and LCVA. Rarefication of the SVC evolved simultaneously to thinning of the common ganglion cell and inner plexiform layer (GCIP) after ON. No alterations of the deep vascular complex were seen in eyes with ON, and no alterations of the retinal vasculature were recognized in patients having acute non-ON relapses. Discussion: Rarefication of the SVC and growing of the FAZ evolve rapidly after ON and are linked to persistent visual disability. ON-related SVC thinning might be closely linked to GCIP atrophy and might occur due to an altered local metabolic activity within inner retinal layers.